HCV Infection in Thalassemia Syndromes and Hemoglobinopathies: New Perspectives - Maffei, Laura; Sorrentino, Francesco; Caprari, Patrizia; Taliani, Gloria; Massimi, Sara; Risoluti, Roberta; Materazzi, Stefano (Frontiers in Molecular Biosciences, 2020)
Hepatitis C virus (HCV) infection is one of the most serious complications of transfusion therapy in the thalassemia and sickle cell disease population before 1990; in fact, since 1990 serological tests were made available to detect infection in blood donors. The iron chelation therapy has improved the life expectancy of these patients and, consequently, a decrease in death due to heart disease is observed, as well as an increase in liver disease due to the iron overload and HCV infection that lead to liver fibrosis, cirrhosis, and hepatocellular carcinoma. Until few years ago, the recommended therapy for HCV treatment consisted of pegylated-interferon alpha plus ribavirin, a therapy with important side effects. This treatment has been severely limited to thalassemic and SCD patients due to the hemolytic anemia induced by ribavirin causing an increase in the number of blood transfusions. The development of highly effective Direct-acting Antiviral Agents towards different viral genotypes has led to a real HCV eradication with negative viremia and sustained viral response between 90 and 98%. At the beginning some indications of Direct-acting Antiviral Agents administration were available for those patients exhibiting advanced cirrhosis or needing liver transplantation over time for the high costs of new drugs. Recently, all treatment regimens can be used for patients with various HCV genotypes, different stages of liver disease, and comorbidities. The HCV eradication has also led to a marked improvement in the parameters of martial accumulation, demonstrating a synergic action also between the effect of antiviral therapy and iron chelation.